The Auckland Cataract Study: 2 year postoperative assessment of aspects of clinical, visual, corneal topographic and satisfaction outcomes - Thompson, A M (Copyright 2004 British Journal of Ophthalmology, 2004)
Aim: To assess clinical, visual, computerised corneal topographic, and subjective satisfaction with visual acuity, in a cohort of subjects 2 years after phacoemulsification surgery in a public hospital in New Zealand. Methods: Prospective study of a representative sample of 97 subjects (20%) randomly selected from 480 subjects in the original Auckland Cataract Study (ACS) cohort. The clinical assessment protocol was identical to the ACS and included an extensive questionnaire to enable direct comparisons to be made between the two groups. Results: The study population was predominantly female (66%) with a mean age of 76.3 (SD 9.9) years. New systemic and ocular disease affected 18.4% and 10.3% of subjects respectively, and 10.3% required referral to either a general practitioner (2.1%) or ophthalmologist (8.2%). Mean best spectacle corrected visual acuity (BSCVA) was 0.2 (0.2) logMAR units (6/9 Snellen equivalent), with mean spherical equivalent −0.37 (1.01) dioptres (D) and astigmatism −1.07 (0.70) D 2 years postoperatively, compared to mean BSCVA 0.1 (0.2) logMAR units (6/7.5 Snellen equivalent), spherical equivalent −0.59 (1.07) D, and astigmatism −1.14 (0.77) D 4 weeks after surgery. 94.9% of subjects retained a BSCVA of 6/12 or better, irrespective of pre-existing ocular disease. The overall posterior capsule opacification (PCO) rate was 20.4% and this was visually insignificant in all but 3.1% of eyes that had already undergone Nd:YAG posterior capsulotomy. Orbscan II elevation technology demonstrated corneal stability 2 years after uncomplicated phacoemulsification. Although corneal astigmatism was eliminated in approximately half of the subjects 1 month postoperatively, astigmatism showed a tendency to regress towards the preoperative level with local corneal thickening at the site of incision 2 years after cataract surgery. Of fellow eyes, 61.2% had undergone cataract surgery. Overall, 75.3% of subjects were moderately to very satisfied with their current level of visual acuity. Conclusion: Two years after cataract surgery subjects are generally satisfied with their current level of vision and distance BSCVA is 6/12 or better in the majority of eyes. Although only a minority of eyes develop sufficient PCO to require capsulotomy 10.3% of eyes develop new vision threatening ocular pathology.